2022
DOI: 10.3390/vaccines10070994
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Determinants of COVID-19 Vaccination Uptake Were Different between Chinese Diabetic Inpatients with and without Chronic Complications: A Cross-Sectional Survey

Abstract: The health of people with chronic diabetes mellitus (DM) complications will worsen following coronavirus disease 2019 (COVID-19) infection. This cross-sectional study compared perceptions and factors related to COVID-19 vaccination uptake between subgroups of DM inpatients with and without chronic complications in China. A multivariate logistic regression model was used for data analysis. Of the 645 participants, those without any complications reported significantly higher uptake of at least one dose of COVID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
1
3
1
Order By: Relevance
“…One interesting nding of this study was the nonsigni cant in uence of the perceived severity of COVID-19 infection on the likelihood of receiving full vaccination among persons with DM. This nding contradicts ndings from other studies conducted among persons with DM in China (19,36). This contradiction is potentially explained by the different patterns of the pandemic with fewer reported COVID-19 cases and deaths in Uganda than in Eastern Asia (1).…”
Section: Perceptions Of Full Covid-19 Infection and Covid-19 Vaccinationcontrasting
confidence: 97%
See 1 more Smart Citation
“…One interesting nding of this study was the nonsigni cant in uence of the perceived severity of COVID-19 infection on the likelihood of receiving full vaccination among persons with DM. This nding contradicts ndings from other studies conducted among persons with DM in China (19,36). This contradiction is potentially explained by the different patterns of the pandemic with fewer reported COVID-19 cases and deaths in Uganda than in Eastern Asia (1).…”
Section: Perceptions Of Full Covid-19 Infection and Covid-19 Vaccinationcontrasting
confidence: 97%
“…Having a comorbidity potentially increases the perceived risk of severe COVID-19 outcomes among people with DM making them less hesitant to accept COVID-19 vaccination (19,33). However, interestingly, this study revealed that more participants with a strongly perceived severity of COVID-19 were not fully vaccinated than were those with a weakly perceived severity of COVID-19 infection, a nding that supports the notion that perceived severity is less likely to predict health behavior (23).…”
Section: Perceptions Of Full Covid-19 Infection and Covid-19 Vaccinationsupporting
confidence: 71%
“…The same checklist was used to measure self-reported adverse events of COVID-19 vaccination among general population 39 and diabetic patients in China. 40 …”
Section: Methodsmentioning
confidence: 99%
“…Higher COVID-19 vaccine coverage among people with comorbidities in the UK might be explained by the fact that the UK used risk-based scheduling that prioritized people with comorbidities, e.g., hypertension and type 2 diabetes, for early vaccination ( 49 ). A study in China found that only 25.1% of people with diabetes mellitus received COVID-19 vaccination and this proportion was far below the rate in the general population (88%) ( 50 ). Furthermore, hospitalized patients with diabetes mellitus and chronic complications had a lower COVID-19 vaccine coverage (11.2%) than those without chronic complications (43.2%).…”
Section: Discussionmentioning
confidence: 99%